IMPLEMENTASI MODEL CREATIVE DANCE PADA PEMBELAJARAN SENI TARI MAHASISWA PGSD UNIVERSITAS SARJANAWIYATA TAMANSISWA - Dyan Indah Purnama Sari; Poppy Indriyanti (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2019)
This article studied the creative dance model implementation in dance teaching for PGSD students, this article is formulated so that (1) PGSD Universitas Sarjanawiyata Tamansiswa students know how to create children dance, (2) PGSD Universitas Sarjanawiyata Tamansiswa students can create children dance by using creative dance model, (3) in the creation process, PGSD Universitas Sarjanawiyata Tamansiswa students can develop their creative idea, (4) PGSD students become active, creative, and innovative students in the process of creating children dances. Additionally, this article also aims at analyzing the role of creative dance model in the creation of children dance in Dancing Art teaching. The creative dance model is often referred to as creation model. The approach used in this research is qualitative research which applied a descriptive analysis method aimed at describing, summarizing various conditions, various situations, or various social reality phenomena in the community. The data collection was conducted by means of observation, interview, and documentation. The product of this research would be a teaching model that can be used as a guide or manual in the process of construction and exploration of children dance to be used by PGSD students, especially PGSD Universitas Sarjanawiyata Tamansiswa students.